SISTEM KASIR PENYIMPANAN DATA TRANSAKSI DAN BARANG MASUK PADA TOKO RZ KIDS TEMBILAHAN BERBASIS CLOUD - Zulrahmadi; Fanisha Juliananda Putri; Cici Nurmalayuni (Fakultas Ekonomi dan Bisnis, 2025)
This study aims to design and build a web-based cashier application equipped with transaction data storage features to facilitate the sales process and data management at the RZ Kids Store. The system development method used is waterfall, starting from the needs analysis stage, design, implementation, to testing. This application is built using the Python programming language with the Flask framework, and uses SQLite as a data storage medium. The results of the test show that the application can run well, record every sales transaction automatically, and produce daily and monthly sales reports that are neatly stored. With this application, the transaction process becomes faster, more efficient, and has minimal errors, and helps shop owners in making data-based decisions.